A snapshot of sediment dynamics on an inshore coral reef. (November 2022) - Schlaefer, Jodie A.; Tebbett, Sterling B.; Bowden, Casey L.; Collins, William P.; Duce, Stephanie; Hemingson, Christopher R.; Huertas, Victor; Mihalitsis, Michalis; Morais, Juliano; Morais, Renato A.; Siqueira, Alexandre C.; Streit, Robert P.; et al.
Abstract: Sediments are ubiquitous on coral reefs. However, studies of reef sediments have largely focused on isolated reservoirs, or processes, and rarely consider hydrodynamic drivers. We therefore provide a quantitative snapshot of sediment dynamics on a coral reef. Across a depth profile, we simultaneously examined: suspended sediments, sediment deposition and accumulation, and hydrodynamic and biological movement processes. We reveal the marked potential for the water column to deliver sediments. Currents carried 12.6 t of sediment over the 2, 314 m 2 study area in 6 days. Sediment traps suggested that a surprisingly high percentage of this sediment was potentially deposited (5.2%). Furthermore, wave-driven resuspension and reworking by parrotfishes separated a highly dynamic sediment regime on the shallow reef flat (3 m), from a more stagnant reef slope (4.5 m–12 m). This study provides a comprehensive model of how hydrodynamic forces and on-reef processes may shape sediment dynamics on a coral reef. Highlights: Suspended sediments and sediment deposition in TurfPods and traps was quantified. Sediment movement via waves, currents, and parrotfishes was measured concurrently. Algal turf proxies readily trapped suspended sediments with fast accumulation rates. Wave energy and parrotfish reworking separated sediment dynamics across habitats. Replicating our approach spatially and temporally may provide further key insights.